PENERAPAN KEGIATAN TAHFIDZ DI TAMAN KANAK-KANAK SEMEN PADANG - Restha Ramadhani; Asdi Wirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the uniqueness of the implementation of tahfidz activities at Semen Padang Kindergarten, which makes tahfidz one of the flagship programs in the field of Islam in accordance with its motto, namely